Futuro esquecido: a recepção da ficção cyberpunk na América Latina - Londero, Rodolfo Rorato (2011)
The aim of this research is to discuss the reception of Latin American cyberpunk fiction, in other words, the Latin American reception of cyberpunk fiction. The cyberpunk fiction emerged in North American social and economic context in the 1980 s, and it depicts several topics linked to place and moment of production: the failed States and neoliberalism; the emergence of cyberspace and free circulation of capital beyond national borderlines; the dystopian background, the disbelief in future and grand narratives collapse as it is proposed by the lyotardian postmodernity, etc. These characteristics lead to identify the cyberpunk fiction as the supreme representation of late capitalism (Jameson). However, how can the cyberpunk fiction in Latin America be thought, it means, a place that is inside and outside of the world system at the same time? The hypothesis of this research points out to utopian way of Latin American cyberpunk fiction that does not exist in North American version. The representation of utopia in this fiction is only possible due to places out of world system: marginalized urban groups, Indian ethnics, ecological enclaves, religious movements, etc. This research is composed by four chapters: the first one discusses science fiction, while a genre which involves cyberpunk fiction, contesting its values (ephemerality, particularity and imitation) in face to mainstream literature (eternity, universality and originality); the second one approaches the Marxist model base-superstructure, which is considered pertinent to analyze the relationship between text and context; the third one verifies the kind of reception produced by Latin American cyberpunk fiction, in order to that, it is elected the Argentinean magazine Neuromante Inc. as a sample of this reception; and the forth one analyzes some novels in order to prove the hypothesis: Mañana, las ratas ( Tomorrow, the rats , 1977), by José B. Adolph; Silicone XXI ( Silica 21st century , 1985), by Alfredo Sirkis; Flores para un cyborg ( Flowers for a cyborg , 1996), by Diego Muñoz Valenzuela; 2010: Chile en llamas ( 2010: Chile in flames , 1998), by Darío Oses; El viaje ( The trip , 2001), by Rodrigo Antezana Patton; El delirio de Turing ( Turing s Delirium , 2003), by Edmundo Paz Soldán; De cuando en cuando Saturnina ( From time to time Saturnina , 2004), by Alison Spedding; A mão que cria ( The hand that creates , 2006), by Octavio Aragão; La segunda enciclopedia de Tlön ( The second encyclopedia of Tlön , 2007), by Sergio Meier; Os dias da peste ( The days of the plague , 2009), by Fábio Fernandes; and Cyber Brasiliana (2010), by Richard Diegues.